Association between frailty syndrome and family functioning among older adults with diabetic retinopathy - Olmos Valencia, Jesús Enrique (2024)
Objective: To determine the association between frailty syndrome and family functioning among older adults with diabetic retinopathy. Materials and methods: An analytical and cross-sectional study conducted among patients diagnosed with diabetic retinopathy. The ophthalmology department diagnosed diabetic retinopathy through pupil dilation, using tetracaine and an ophthalmoscope. Three groups were determined using the FRAIL questionnaire: frail, prefrail and nonfrail; the sample sizes were 39, 64 and 76, respectively, matched by age. The study variables included age, sex, education, marital status and occupation. Additionally, the time since the diagnosis of diabetic retinopathy was measured. Furthermore, the type of family was determined according to Huerta’s classification, which identifies nuclear family, extended family, composite extended family, single-parent family and blended family. Family functioning was evaluated with the FF-SIL questionnaire. The statistical analysis included the chi-square test. The protocol was registered with the research and ethics committee of the health institution, and surveys were administered after obtaining prior informed consent.  Results: The median ages in the frail (73 years), prefrail (71 years) and nonfrail (70 years) groups were statistically similar (p = 0.061). The prevalence of living as a couple was 23.1 % in the frail group, 48.4 % in the prefrail group and 60.5 % in the nonfrail group, with statistically significant differences among these groups (p = 0.001). There was an association between frailty syndrome and type of family functioning: in the nonfrail group, 88.2 % had a functional family, compared to 46.9 % in the prefrail group and 15.4 % in the frail group (p = 0.000). Conclusions: There is an association between frailty syndrome and family functioning among geriatric patients with diabetic retinopathy.